Questions of General Pedagogy in Higher Education - Shepelyuk, Olga L. (2020)
At present, the growth of individual independence and activity, the change in its orientations and values requires changes in the issue of professional. The article carries out a serious study on the importance of general pedagogical concepts in modern Russian society. General issues of pedagogy determine the conceptual significance of the pedagogical process as a whole. In the article, the author formulates the concept of education in a broad social sense, reveals its pedagogical essence, describes the characteristic properties. Also, through the prism of such a science as pedagogy, the author expands and considers such categories as teaching, didactics, and identifies his author's aspects of understanding these categories. An important issue in the article is the relationship of pedagogy with other sciences, which are its methodological basis.